Endoplasmic reticulum stress triggers unfolded protein response as an antiviral strategy of teleost erythrocytes - Salvador-Mira, Maria; Sanchez-Cordoba, Ester; Solivella, Manuel; Nombela, Ivan; Puente-Marin, Sara; Chico, Veronica; Perez, Luis; Perez-Berna, Ana Joaquina; Ortega-Villaizan, Maria del Mar (Frontiers in Immunology, 2024)
IntroductionFish nucleated red blood cells (RBCs), also known as erythrocytes, play a crucial role in maintaining immune system balance by modulating protein expression in response to various stimuli, including viral attack. This study explores the intriguing behavior of rainbow trout RBCs when faced with the viral hemorrhagic septicemia virus (VHSV), focusing on the endoplasmic reticulum (ER) stress and the unfolded protein response (UPR).MethodsRainbow trout RBCs were Ficoll-purified and exposed to ultraviolet (UV)-inactivated VHSV or live VHSV at different multiplicities of infection (MOIs). Using cryo-soft X-ray tomography (cryo-SXT), we uncovered structural and cellular modifications in RBCs exposed to UV-inactivated VHSV. Moreover, RBCs were treated with 4-phenylbutyric acid (4-PBA), an ER stress inhibitor, to investigate its effect on viral replication. Quantitative real-time PCR was also used to analyze the expression of genes related to the UPR and other related cellular pathways.Results and discussionBeyond their antiviral response, RBCs undergo notable intracellular changes to combat the virus. Cryo-SXT highlighted a significant increase in the ER volume. This increase is associated with ER stress and the activation of the UPR pathway. Interestingly, VHSV replication levels augmented in RBCs under ER-stress inhibition by 4-PBA treatment, suggesting that rainbow trout RBCs tune up ER stress to control viral replication. Therefore, our findings suggested the induction of ER stress and subsequent activation UPR signaling in the antiviral response of RBCs to VHSV. The results open a new line of investigation to uncover additional mechanisms that may become novel cellular targets for the development of RBC-targeted antiviral strategies.